Aspects of modern monetary and macroeconomic policies / edited by Philip Arestis, Eckhard Hein and Edwin Le Heron. - Arestis, Philip, 1941-; Hein, Eckhard, 1963-; Le Heron, Edwin, 1956- (Palgrave Macmillan, 2007)
Over the last 30 years or so the developments in the area of monetary and macroeconomic policies have been quite substantial. Within the new consensus macroeconomics (NCM), monetary policy is upgraded while fiscal policy is downgraded. This new monetary policy has been the main instrument of policy under the guise of inflation targeting, an approach pursued by a number of central banks worldwide. In this book a number of questions relating to this new monetary and macroeconomic policy approach are raised. NCM is compared to post-Keynesian alternatives on a theoretical level and the consequences of NCM for economic policy outcomes and macroeconomic performance are discussed. Finally, the book covers some empirical studies on recent monetary and macroeconomic policies in the Euro area, Germany and the UK.